Penerapan Kompres Hangat Pada Demam Thypoid Di Ruang Anyelir Rsud Waled Kabupaten Cirebon - Mamay maftuha, Indah; Sari Purbaningsih, Endah; Sindia Devi, Nadia; Khasanah, Uswatun; Rimawati Nurokhman, Neneng (MEJORA Medical Journal Awatara, 2024)
Infectious diseases are one of the main health problems in developed and developing countries, one of them is because Typhoid fever. This study aims to Application of Warm Compresses for Typhoid Fever in the Anyelir Ward at Waled District Hospital, Cirebon Regency. The research method used is descriptive research in the form of a case study. The respondents in this study were child patients with typhoid fever in the Anyelir ward at Waled Hospital, Cirebon Regency. The results of a case study of nursing care applied to an.s with typhoid fever in the form of warm compresses for 15 minutes in one day showed that the family said the fever had begun to decrease, anxiety decreased, red skin decreased, body temperature was 37.30C. From the case studies that have been carried out, it can be concluded that warm compresses have an effect on reducing body temperature in children with typhoid fever with the results of the family saying that the fever has started to decrease, anxiety has decreased, red skin is no longer there, body temperature is 37.30C.